The impact of perceived organisational support, supervisor support and self-efficacy on Transfer of Training among Public Service Officers/ Noor'ain Mohamad Yunus, Norisham Sharuddin and Mohd Khalid Mohd Abas - Mohamad Yunus, Noor'ain; Sharuddin, Norisham; Mohd Abas, Mohd Khalid (2022)
Transfer of training practice in the public sector is crucial to ensure excellent service deliverables. Return on investment, active learning, and applying new attitudes, skills, and knowledge from training can be rewarding for both parties. Despite training transfer being the most significant factor in training effectiveness, it has become one of the most critical challenges for an organisation. However, a limited number of training transfer studies were conducted in Malaysia, particularly in public service. Therefore, this study investigated gaps in training transfer among public service officers. A cross-sectional study was conducted between April to May 2021 to examine the relationship between the variables. A total of 125 public service officers in Putrajaya were recruited. Findings revealed a significant relationship between supervisor support and self-efficacy with the transfer of training. Understanding these associations may help training policymakers to design strategies to enhance the quality of training.